Renewability assessment of a production system: Based on embodied energy as emergy. (May 2016) - Shao, Ling; Chen, G.Q.
Abstract: Based on a comprehensive review of previous renewability assessment studies, the present work contributes a framework to assess the renewability of a production system based on the systems ecological concept of embodied energy as emergy (embodied solar energy). An input–output analysis based transformity database is adopted to concretely trace the renewable and nonrenewable resources embodied in the supply chain for all product materials. A renewability index as the percentage of total renewable resources over the total resources used for the production process is devised to assess the renewability of a production system. The renewability assessment of a typical wastewater treatment system in Beijing is performed as a case study to illustrate the framework in context of water–energy nexus. The renewability index of the case system is evaluated around 13%, and fossil energy is revealed as a key source for total resources use. The presented framework is shown to have broad application prospects and can be very useful in sustainability studies.